2011
DOI: 10.23939/chcht05.01.115
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymers for Food Packing – Factors Influencing their Degradation and Certification Types – a Comprehensive Review

Abstract: In this paper an overview of novel biodegradable polymers for food packaging is presented. The aim was to present factors influencing polymer degradation and biodegradation in various environments. It was noted that biodegradable polymers are an imperfect alternative for classical polymers and their decomposition strongly depends on degradation environment. It was also shown that there are various approaches in different countries to certification of biodegradable polymer materials, which rather complicates it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 48 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…and lipids. They can be used alone or mixed with a biodegradable synthetic polymer such as polycaprolactone (PCL) or other biodegradable polyesters such as polylactic acid (PLA) (Guzman et al, 2011;Rameshkumar et al, 2020). These materials used in the production of food packaging have good gas barrier properties (Avérous and Pollet, 2012).…”
Section: Polymers Directly Extracted From Natural Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…and lipids. They can be used alone or mixed with a biodegradable synthetic polymer such as polycaprolactone (PCL) or other biodegradable polyesters such as polylactic acid (PLA) (Guzman et al, 2011;Rameshkumar et al, 2020). These materials used in the production of food packaging have good gas barrier properties (Avérous and Pollet, 2012).…”
Section: Polymers Directly Extracted From Natural Materialsmentioning
confidence: 99%
“…It is obtained from various sources such as cassava, potato, corn, wheat, rice, sweet potato (Whistler and BeMiller, 2007). It is composed of amylose and amylopectin which ratios vary with the source of the starch (Guzman et al, 2011). Several studies have shown that starch is a thermoplastic material (TPS) and can be used to replace polystyrene (PS) which is a non-biodegradable compound.…”
Section: Polymers Directly Extracted From Natural Materialsmentioning
confidence: 99%
“…10 Furthermore, as a matrix material, starch tends to become brittle with age due to dehydration and free volume relaxation. Nevertheless, by combining starch with other biodegradable components, starch-based composites with excellent functional properties have been developed.…”
Section: Gregory M Glenn Syed H Imam and William J Ortsmentioning
confidence: 99%
“…[5][6][7] Starch itself continues to be extensively investigated as a replacement for plastics used in single-use food and beverage containers because of its compatibility with the environment. [8][9][10] It is a renewable resource that degrades readily in composting conditions and in many landscape and aquatic environments. It is easily metabolized by micro-organisms and mammals alike and therefore does not accumulate in the food chain the same way as plastics, especially in marine environments.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers stay long within the environment after the final use creating significant environmental pollution. This demands to explore new biodegradable packaging materials from renewable sources and it became a topic of great interest in the recent past [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%